Development of Surface Fluorescence X‐Ray Absorption Fine Structure Spectroscopy Using a Laue‐Type Monochromator. Issue 7 (8th August 2018) - Wakisaka, Yuki; Kido, Daiki; Uehara, Hiromitsu; Yuan, Qiuyi; Feiten, Felix E.; Mukai, Shingo; Takakusagi, Satoru; Uemura, Yohei; Yokoyama, Toshihiko; Wada, Takahiro; Uo, Motohiro; Sekizawa, Oki; et al.
Abstract: Surface fluorescence X‐ray absorption fine structure (XAFS) spectroscopy using a Laue‐type monochromator has been developed to acquire structural information about metals with a very low concentrate on a flat highly oriented pyrolytic graphite (HOPG) surface in the presence of electrolytes. Generally, surface fluorescence XAFS spectroscopy is hindered by strong scattering from the bulk, which often chokes the pulse counting detector. In this work, we show that a bent crystal Laue analyzer (BCLA) can efficiently remove the scattered X‐rays from the bulk even in the presence of solution. We applied the technique to submonolayer (∼10 14 atoms cm −2 ) Pt on HOPG and successfully obtained high signal/noise in situ XAFS data in combination with back‐illuminated fluorescence XAFS (BI‐FXAFS) spectroscopy. This technique allows in situ XAFS measurements of flat electrode surfaces to be performed in the presence of electrolytes. Abstract : BCLA+BI‐XAFS method for the model fuel cell catalyst